Roadmap on biological pathways for electronic nanofabrication and materials. Issue 1 (9th January 2019) - Bathe, Mark; Chrisey, Linda A; Herr, Daniel J C; Lin, Qinghuang; Rasic, Daniel; Woolley, Adam T; Zadegan, Reza M.; Zhirnov, Victor V
Abstract: Conventional microchip fabrication is energy and resource intensive. Thus, the discovery of new manufacturing approaches that reduce these expenditures would be highly beneficial to the semiconductor industry. In comparison, living systems construct complex nanometer-scale structures with high yields and low energy utilization. Combining the capabilities of living systems with synthetic DNA-/protein-based self-assembly may offer intriguing potential for revolutionizing the synthesis of complex sub-10 nm information processing architectures. The successful discovery of new biologically based paradigms would not only help extend the current semiconductor technology roadmap, but also offer additional potential growth areas in biology, medicine, agriculture and sustainability for the semiconductor industry. This article summarizes discussions surrounding key emerging technologies explored at the Workshop on Biological Pathways for Electronic Nanofabrication and Materials that was held on 16–17 November 2016 at the IBM Almaden Research Center in San Jose, CA.